Voice and Little v and VO–OV Word‐Order Variation in Chinese Languages. (11th March 2021) - Sybesma, Rint
Abstract: This article addresses some issues related to Voice and little v. It does so by discussing and analyzing the variation that exists in the Chinese language family with respect to object placement (VO versus OV). It turns out that this variation can be accounted for straightforwardly as long as we assume, first, that Voice and v are sometimes split and sometimes bundled, even within one language, and, second, that Voice does not always select vP; it can also select VP.